Analysis of factors contributing to the dispersal of Casuarina junghuhniana Miq. in a volcanic mountain - Brian Rahardi; Serafinah Indriyani; Luchman Hakim; Agus Suryanto (Brawijaya University, 2020)
Casuarina junghuhniana or mountain ru, she oak or cemara is a species from Indonesia which grows in the highland area at an altitude between 2000 - 3000 m above sea level (asl). One of the highland area in Eastern Java (Jawa Timur) of Indonesia is Bromo Tengger Semeru National Park (TNBTS). The study site was on the Tengger Sea of Sands, Eastern Java, Indonesia where it is affected by volcanic activity. This tree, from some references, has not been well studied yet although it has been reported as a tree native to Indonesia. The lack of the study poses problems when there is a program related to planting the tree on a certain location in TNBTS for rehabilitation purposes. This study attempted to construct a Structural Equation Model that mapped some factors observed in the study site related to C. junghuhniana population. Explored factors for their relationship with each other included the number of male and female individuals, growth-related indicators, and environmental factors consisting of altitude and the tree population. Formative factors which consist of parameters related to growth, environmental factors and factor associated with the diffusion of new individuals, may contribute to population growth while population growth was the opposite. The individual growth might not significantly contribute to the population of C. junghuhniana; instead, the population growth was affected by the tree individuals. Generative reproduction contributed the least to the dispersal as it may rely more on vegetative reproduction by adventitious shoots from roots.